OPTIMIZING THE ROLE OF ISLAMIC EDUCATION IN THE PROCESS OF SOCIAL STRATIFICATION - Firmansyah; Aslan; Ade Rosad; Erisa Ardika Prasada (Adisam Publisher, 2026)
This study aims to analyze the role of Islamic education in reducing social inequality and improving social stratification in society. The method used in this research is library research by collecting and analyzing relevant literature, including books, scientific journals, articles, and relevant research reports on the relationship between Islamic education and social stratification. This approach allows the author to explore theories and previous findings without being tied to limited primary data. The findings show that Islamic education has great potential to reduce social inequality through teaching universal values such as justice (adl), brotherhood (ukhuwah) and virtue (ihsan). Islamic education also plays a role in providing access to disadvantaged groups and strengthening social awareness that can drive structural change in society. This research implies that Islamic education can be an important pillar in creating a more inclusive and just society. Zakat, infaq, and sadaqah programs integrated in Islamic education have the potential to help marginalized groups, while practical skills-based curricula can open up opportunities for social mobility for individuals from low economic groups. The results of this study recommend the need for collaborative efforts between the government, private sector and communities to overcome challenges in implementing Islamic education, such as limited infrastructure and social stigma. A more integrated strategy for strengthening Islamic education is needed to accelerate the desired social change and create a society free from social inequality.